THE EFFECTIVENESS OF MIND MAPPING TECHNIQUESIN IMPROVING STUDENTS' NARRATIVE TEXT WRITING ABILITY:An Experimental Study in the Second Grade Students of SMA Lab School UPI Bandung - Litani Wahyu Kusumaningsih, - (2008)
The focus of this research was to investigate the effectiveness of Mind Mapping techniques in improving students' narrative text writing ability of 60 students second grader students in SMU Lab School UPI Bandung. It was also to find out the advantages and the disadvantages of using this techniques. A quasi experimental design was used to conduct the research. The samples of this study were XI IPS I as the experimental group, and XI IPS II as the control group. The experimental group was given the treatment, while the control group was not given any treatment. Data collection was taken from pre-test and post-test, and questionnaire. The independent t-test fromula were used to analyze the data from the tests. Meanwhile, the data from questionnaire was analyzed to examine the advantages and the disadavantages of Mind Mapping techniques. The research findings showed that Mind Mapping techniques was effective in improving students' narrative writing ability, especially in pre-writing stages which involving the generating ideas process. Additionally, the data result from questionnaire showed that Mind Mapping techniques had several advantages. First, Mind Mapping techniques eased students to understand the structure and features of narrative text. Second, Mind Mapping techniques helped students made a creative and systematical narrative story. However, the difficulties of the proper vocabulary became one of the disadvantages of Mind Mapping techniques. Moreover ,this techniques also needed a long time consumed in the implementation. This study is expected to give a good contribution for teachers and students in teaching and learning narrative writing.